Nonlinear and Synergistic Effects of ULF Pc5, VLF Chorus, and EMIC Waves on Relativistic Electron Flux at Geosynchronous Orbit. Issue 6 (16th June 2018) - Simms, Laura E.; Engebretson, Mark J.; Clilverd, Mark A.; Rodger, Craig J.; Reeves, Geoffrey D.
Abstract: Using data covering the years 2005–2009, we study the linear and nonlinear responses of log10 relativistic electron flux measured at geosynchronous orbit to ultralow frequency (ULF) Pc5, very low frequency (VLF) lower band chorus, and electromagnetic ion cyclotron (EMIC) waves. We use regression models incorporating a quadratic term and a synergistic interaction term. Relativistic electron fluxes respond to ULF Pc5 and VLF chorus waves both linearly and nonlinearly. ULF Pc5 waves contribute both to electron enhancement (at midrange wave activity) and loss (at high levels of wave activity). Nonlinear effects of VLF chorus are positive (i.e., cause acceleration), adding to the positive linear effects. Synergistic interaction effects between high levels of VLF chorus and midrange values of ULF Pc5 waves result in more electron acceleration than would be predicted by a simpler additive model. Similarly, the negative effect of EMIC waves (losses) is more influential than would be predicted by a linear model when combined with either VLF chorus or ULF Pc5 waves. During disturbed conditions (high Kp), geostationary electron flux responds more strongly to the same levels of ULF Pc5 and VLF chorus waves. This flux also responds more to ULF Pc5 and chorus waves during southward Bz conditions. Unstandardized regression coefficients for models incorporating nonlinear and synergistic effects of waves are presented for use in future modeling. Key Points: Regression analyses of relativistic electron flux (0.7‐7.8 MeV) show both linear and nonlinear response to wave activity High chorus intensity and midrange ULF Pc5 power result in more electron acceleration than would be predicted by an additive model The negative effect of EMIC waves is greater if combined with either chorus or ULF Pc5 waves